ULTRAHIGH SPEED SWEPT SOURCE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY OF RETINAL AND CHORIOCAPILLARIS ALTERATIONS IN DIABETIC PATIENTS WITH AND WITHOUT RETINOPATHY. Issue 1 (January 2017) - Choi, WooJhon; Waheed, Nadia K.; Moult, Eric M.; Adhi, Mehreen; Lee, ByungKun; De Carlo, Talisa; Jayaraman, Vijaysekhar; Baumal, Caroline R.; Duker, Jay S.; Fujimoto, James G.
Abstract : Purpose: To investigate the utility of ultrahigh speed, swept source optical coherence tomography angiography in visualizing retinal microvascular and choriocapillaris (CC) changes in diabetic patients. Methods: The study was prospective and cross-sectional. A 1, 050 nm wavelength, 400 kHz A-scan rate swept source optical coherence tomography prototype was used to perform volumetric optical coherence tomography angiography of the retinal and CC vasculatures in diabetic patients and normal subjects. Sixty-three eyes from 32 normal subjects, 9 eyes from 7 patients with proliferative diabetic retinopathy, 29 eyes from 16 patients with nonproliferative diabetic retinopathy, and 51 eyes from 28 diabetic patients without retinopathy were imaged. Results: Retinal and CC microvascular abnormalities were observed in all stages of diabetic retinopathy. In nonproliferative diabetic retinopathy and proliferative diabetic retinopathy, optical coherence tomography angiography visualized a variety of vascular abnormalities, including clustered capillaries, dilated capillary segments, tortuous capillaries, regions of capillary dropout, reduced capillary density, abnormal capillary loops, and foveal avascular zone enlargement. In proliferative diabetic retinopathy, retinal neovascularization above the inner limiting membrane was visualized. Regions of CC flow impairment in patients with proliferative diabetic retinopathy and nonproliferative diabetic retinopathy were also observed. In 18 of the 51 of eyes from diabetic patients without retinopathy, retinal mircrovascular abnormalities were observed and CC flow impairment was found in 24 of the 51 diabetic eyes without retinopathy. Conclusion: The ability of optical coherence tomography angiography to visualize retinal and CC microvascular abnormalities suggests it may be a useful tool for understanding pathogenesis, evaluating treatment response, and earlier detection of vascular abnormalities in patients with diabetes. Abstract : Swept source optical coherence tomography angiography visualizes retinal and choriocapillaris microvasculature alterations in diabetic patients with and without retinopathy.